Analysis of Traditional Fishermen's Income and Productivity on the Welfare Level of the Community in Kwala Besar Village: Analisis Pendapatan dan Produktivitas Nelayan Tradisional terhadap Tingkat Kesejahteraan Masyarakat di Desa Kwala Besar - Syahfitri, Sally; Rizky, M. Chaerul; Ardhana, Meia Syahvani; Gresya, Dearni; Tias, Nurul Purnaning (Indonesian Journal of Innovation Studies, 2025)
Background: Coastal communities, particularly traditional fishermen, face persistent socio-economic challenges that hinder their well-being. Specific Background: In Desa Kwala Besar, Kecamatan Secanggang, Kabupaten Langkat, traditional fishermen depend heavily on income and productivity for their livelihoods. Knowledge Gap: However, empirical evidence on how these two factors simultaneously influence community welfare in this specific context remains limited. Aim: This study aims to analyze the effect of income and productivity on the welfare of traditional fishing communities. Results: Using a quantitative associative approach with 44 purposively selected respondents, the research instruments were validated (r > 0.2973; p < 0.05) and deemed reliable (Cronbach’s Alpha: Income 0.859; Productivity 0.914; Welfare 0.896). Normality was confirmed (Kolmogorov-Smirnov sig. 0.200 > 0.05), and multicollinearity was absent (Tolerance 0.653; VIF 1.531). Regression analysis indicated that both income and productivity significantly and positively affect community welfare. Novelty: This study contributes original data on traditional fishermen in Langkat, integrating multiple socioeconomic indicators within a robust statistical framework. Implications: The findings highlight income and productivity enhancement as strategic levers for sustainable welfare improvement in coastal fishing communities.  Highlights:  Demonstrates the simultaneous impact of income and productivity on welfare. Uses validated and reliable instruments in a coastal village context. Offers evidence-based strategy for sustainable welfare improvement. Keywords: Fishermen Income, Labor Productivity, Community Welfare, Coastal Economy